Analisis Marketing Mix pada PT.Wafdullah Tamu Mulia Cabang Bengkulu dalam Menghadapi Persingan Pasar Kota Bengkulu - Yuni, Yuni; Sriwahyuni, Eka; Shar, Aan (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to determine the application of the marketing mix and also the obstacles faced by PT. Wafdullah Tamu Mulia Bengkulu Branch in market competition. This research method is a type of qualitative research. Data collection techniques used were observation, interviews and documentation and the number of informants was 8 people consisting of employees and congregants. The results of this research are that PT. Wafdullah Tamu Mulia Bengkulu Branch has implemented a marketing mix in market competition which can be seen firstly, the product focuses on offering regular Umrah packages, Umrah plus, full Ramadhan Umrah, Furoda Hajj and Smart Hajj secondly, the prices offered are affordable by the third congregation, the place is very strategically located and easy to find in the middle of the fourth city of Bengkulu province, the promotion is in accordance with the marketing concept starting from advertising with social media and also interacting directly door to door. Cost limitations are one of the obstacles in competition for Hajj and Umrah organizers where high operational costs can be an obstacle in improving service quality because every pilgrim has the right to choose and assess a Hajj and Umrah organizer. So that PT. Wafdullah Guest Mulia's Bengkulu branch has effective and efficient operational costs to improve service quality. Keywords: Hajj And Umrah, Market Competition, Marketing Mix.